Donner sens au sida - Guillaume Lachenal (Genre, Sexualité et Société)
This article is a commentary of a text by Paula Treichler« AIDS, homophobia and biomedical discourse: an epidemic of signification ». Written in the first years of the AIDS epidemic, Treichler’s article has been immensely influential. After a brief presentation of the scientific context at the time of the publication (Semiotic turn, works by Bruno Latour and Steeve Woolgar), the commentary insists on the contemporary relevance of the text: the work consisting in “making sense” of the epidemic is always to be done.